PROSEDUR REKRUTMEN TENAGA PENDIDIK (GURU) - Junia Dinda Putri; Elva Sabina; Delvi Zul Hidayat; Rizki Ananda; Nasrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article examines the recruitment procedures for teaching staff (teachers) in educational institutions. The main objective is to ensure the recruitment of competent and experienced human resources to support quality education. This research uses a qualitative approach, by analyzing relevant laws and regulations and literature on teacher professionalism. The research results show that recruitment of professional teachers is very important for educational institutions, both formal and non-formal. The key is to obtain human resources who truly have the required competencies and experience. This is important because the quality of teachers will greatly determine the quality of learning and education provided to students. If educational institutions can recruit competent and experienced teachers, they will be able to teach optimally and stay at the institution for a long time. Such teachers can provide quality teaching and guidance to students, in line with national education goals. Keywords: education quality, teacher professionalism, teacher recruitment